“You find yourself in a very humiliating situation”: experiences of people living with post-tuberculosis lung disease in Brazil - Almeida, Carlos Podalirio Borges de; Furin, Jennifer Joan; Sumiya, Alberto; Silva, Denise Rossato; Mitnick, Carole Diane (Frontiers in Public Health, 2024)
BackgroundBrazil remains one of the 30 countries with the highest tuberculosis (TB) and TB-HIV coinfection burden. Post-TB lung disease (PTLD) is a set of sequelae that can occur in people who have been cured of TB.AimTo learn about the experiences of people living with PTLD (PLPTLD) and how healthcare workers (HCW) manage PTLD.MethodsAn exploratory qualitative study with a purposive sample of PLPTLD and HCW from two different cities. Open-ended interviews were conducted using a semi-structured interview guide, which were recorded and transcribed. Two researchers analyzed the interviews using an inductive approach and applied a content analysis framework to define categories.ResultsForty-six participants were interviewed, and four categories emerged: PTLD as a social disease; stigma; the fragility of access; and limitations. The categories encompassed two main aspects like PTLD in activities of daily living and emotions in everyday life, for instance, challenges with preparing meals, getting a job, barriers to set clinical appointments or getting social assistance, and stigma.ConclusionThis study reveals specific needs from patients and providers such as a lack of knowledge about PTLD, physical limitations, and stigmatization due to PTLD. It is crucial to address these issues in public health policies.